Synthesizing Satori: A Comparative Analysis of Zen and Psychedelic Mystical Experiences - Christ, Challian (Université d'Ottawa / University of Ottawa, 2023)
This thesis investigates the acute phenomenology of altered states of consciousness induced through psychedelics and various Zen practices through the lens of comparative mysticism. Through inductive reasoning, tentative conclusions are drawn regarding how the acute phenomenological qualities of these states compare to one another. This topic had not been meaningfully studied, so the data from which these conclusions were drawn is limited. Though these findings are tentative, they have important implications for the study of comparative mysticism involving psychedelics, and for policy decisions regarding the credentialing of newly trained psychedelic therapists. Further research is required to draw more definitive conclusions on whether psychedelics users and Zen practitioners are having the same sorts of experiences, and this thesis identifies some of the theoretical challenges that can be expected with such research, particularly with regards to the reliability of qualitative data collection methods. To address these challenges, a novel theoretical approach to the study of comparative mysticism involving psychedelic and non-psychedelic altered states of consciousness has been developed.
Keywords: psychedelics; Zen; Buddhism; mysticism; phenomenology; altered states of consciousness; contemplative science; perennialism; constructivism; philosophy of mind